The Value of Education Character in The Legend Stories of The Ternate Community - Agus Hi Jamal; Adelina Ibrahim (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
So far, the culture of North Maluku has not been studied or put in order, so the way it is thought that it would be lost to foreign influence, which is particularly strong in the 21st century, needs governments to make an effort to preserve. formal community which is currently the base of civilization, particularly the informal one Rather, really, given the depth of research, local culture will nurture and help to grow the national culture. Therefore, it must be consistently implemented in education, and accomplish national educational objectives due to the integration of local values. However, as this era's cultural significance is erodes, this as an issue that must be researched as a challenge emerges. It's implied that generations still have a concern for the group that must be rooted in the culture so that the next generation has the ability to fulfill the pledge that this ancestral heritage represents inheritize and formalize such as books and journals so that carry the traditions into the future can be passed on to future generations The data used in this analysis, is the source of the original data. The primary data for the study will be taken from this source, which is collected directly and instantly from the source itself. the aim of the goal is for research in Takome is to conclude that: It is anticipated that a production will be obtained, namely to verify the importance of character education in community legends in the city of Ternate, South District For the long-term preservation of publications, we will record their benefits and values in Ternate, and make them available for the generations to come. Compete in local and national events